Bunkers, Bubbles, Monuments, and Walls: Pathological Narcissism, Nazi Germany, and Donald Trump - Kevin Volkan (EJP import test, 2020)
Summary: Certain physical structures may symbolically represent internal psychological states. Structures, like bunkers, monuments, and walls are especially rich in psychological meaning. These structures are prevalent when pathologically narcissistic leaders are in power. Bunkers and similar structures provide symbolic protection of the good object from being overwhelmed by split off and devalued bad objects. Monuments, on the other hand, externalize the good object into a seemingly invulnerable and permanent structure in the outside world. This sort of bunker mentality was seen during Hitler’s leadership of Nazi Germany and is now evident with Donald Trump, the current president of the of the United States. Bunkers, bunker-like structures, and grandiose monuments provide pathologically narcissistic leaders with a source of adulation that feeds their grandiose self. When the desire to build such structures is accompanied by the projection of bad object characteristics on to specific groups of people, it may be an early indication that the leader suffers from pathological or malignant narcissism.
Keywords: Bunkers; Hitler; Monuments; Narcissism; Object Representation; Trump